Cardioprotective effect of virgin coconut oil in heated palm oil diet-induced hypertensive rats. (September 2015) - Kamisah, Yusof; Periyah, Vengadesh; Lee, Kee Tat; Noor-Izwan, Norrashid; Nurul-Hamizah, Amran; Nurul-Iman, Badlishah Sham; Subermaniam, Kogilavani; Jaarin, Kamsiah; Azman, Abdullah; Faizah, Othman; Qodriyah, Hj Mohd Saad
Abstract Context: Virgin coconut oil (VCO) contains high antioxidant activity which may have protective effects on the heart in hypertensive rats. Objectives: The study investigated the effects of VCO on blood pressure and cardiac tissue by measuring angiotensin-converting enzyme (ACE) activity and its histomorphometry in rats fed with a heated palm oil (HPO) diet. Materials and methods: Thirty-two male Sprague–Dawley rats were randomly divided into four groups: (i) control, (ii) orally given VCO (1.42 ml/kg), (iii) fed with a HPO (15%) diet, and (iv) fed with a HPO diet and supplemented with VCO (1.42 ml/kg, po) (HPO+VCO) for 16 weeks. Blood pressure was measured monthly. After 16 weeks, rat hearts were dissected for lipid peroxidation (TBARS) and ACE activity measurement and histomorphometric study. Results: Systolic blood pressure was significantly increased in the HPO group compared with the control starting at week eight (112.91 ± 1.32 versus 98.08 ± 3.61 mmHg, p < 0.05) which was prevented by VCO supplementation (91.73 ± 3.42 mmHg). The consumption of HPO increased TBARS and ACE activity in heart, which were inhibited by VCO supplementation. The increases in the myofiber width and area as well as nuclear size reduction in the HPO group were significantly prevented by VCO supplementation. Conclusion: These results suggested that VCO supplementation possesses a cardioprotective effect by preventing the increase in blood pressure via an antioxidant mechanism and remodeling in rats fed repeatedly with a HPO diet.